A Sophisticate's Introduction to Database Normalization Theory - Beeri, Catriel; Bernstein, Phil; Goodman, Nathan (International Conference on Very Large Data Bases, 1978)
Formal database semantics has concentrated on dependency constraints, such as functional and multivalued dependencies, and on normal forms for relations. Unfortunately, much of this work has been inaccessible to researchers outside this field, due to the unfamiliar formalism in which the work is couched. In addition, the lack of a single set of definitions has confused the relationships among certain results. This paper is intended to serve the two-fold purpose of introducing the main issues and theorems of formal database semantics to the uninitiated, and to clarify the terminology of the field.